The Influence of Brand Awareness on Consumer Purchase Interest at Oorange Unpad Café Using Multiple Linear Regression Analysis - Alya Zhafirah, Siti; Ardiansah, Irfan Ardiansah (Fakultas Pendidikan Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of brand awareness of the Oorange Unpad Café products on consumer purchasing interest. This research uses a quantitative descriptive multiple linear regression analysis method with the research target, namely respondents consisting of visitors to the Oorange Unpad Café. Based on the results obtained from multiple linear regression analysis, the majority of the five dependent variables show a significant and strong relationship with the independent variables. However, the five multiple linear regression results had P-Value values that were not significant due to several factors that hampered the research. The variable consumer satisfaction with service at Oorange Unpad Café and the variable consumer satisfaction with menu variations at Oorange Unpad Café show the most positive and significant relationship with the independent variables with a Multiple R value of 0.85 and an R Square of 0.72 which is considered quite high compared to other variables.